Crush wounds as an interdisciplinary problem: a description of two clinical cases - Mościcka, Paulina; Cwajda, Justyna B.; Jawień, Arkadiusz; Szewczyk, Maria T. (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2024)
Crush injuries of the lower limbs are a significant problem due to both the complexity of the injury and the significant clinical and socioeconomic burden. Patients most often require multidisciplinary care, because the damage may affect soft tissues, the musculoskeletal system, blood vessels and nerves. Most injuries require surgical treatment. The study presents two case reports of patients who suffered crushing injuries. In one of them, although the patient required amputation of the limb at the shin level, the implemented actions prevented amputation above the knee joint. In the second case report, interdisciplinary activities resulted in the healing of a very extensive wound.